Do warnings received in race walking influence the speed of athletes?. (4th May 2018) - Alves, Danilo L.; Cruz, Ramon; Domingos, Pablo R.; Osiecki, Raul; De Oliveira, Fernando R.; Lima, Jorge R.P.
ABSTRACT: The aim of the study was to measure the influence of bent knee and loss of contact warnings on lap speed in race walkers and correlate with maximum and minimum lap speeds. Fifty-four national race walkers (32 men and 22 women, 22.8 ± 9.0 and 20.7 ± 9.0 years old, respectively) participated in the study. The lap speed pre-warnings, at the moment and post-warnings were compared, with analysis between bent knee and loss of contact. Additionally, the maximum and minimum lap speeds were associated with the lap speed at the moment of warning compared between bent knee and loss of contact. The bent knee warnings were given at lower speeds than loss of contact warnings ( F (1)  = 22.894, p  = 0.001). Additionally, only bent knee warnings negatively influenced the athlete's speed ( F (2)  = 11.430, p  = 0.001) and were associated with the minimum or maximum lap speed in the race ( r  = 0.440, p  = 0.001; r  = 0.201, p  = 0.036, respectively). In conclusion, these findings showed that athletes should avoid very fast or very slow speeds, which reduce the risk of receiving bent knee warnings, and consequently, speed throughout the race.